The Confusion between Pustular Psoriasis and Acute Generalized Exanthematous Pustulosis as a Cause of Exfoliative Dermatitis: A Case Report - Sari, Desiana Widityaning; Damayanti, Damayanti; Anggraeni, Sylvia; Umborowati, Menul Ayu; Cita Rosita Sigit Prakoeswa; Ervianti, Evy (Faculty of Medicine, Universitas Airlangga, 2021)
Background: Pustular psoriasis and Acute Generalized Exanthematous Pustulosis (AGEP) are grouped under pustular diseases, in which their clinical manifestations are similar. Those diseases can lead to exfoliative dermatitis. Purpose:To evaluate a specific histopathological examination in differentiating Pustular Psoriasis and AGEP. Case: A 55-year-old woman presented with sudden redness and diffused scaly skin with multiple pustules and also fever. She had taken Cefadroxil 2 days before the scales and pustules appeared. Leukocytosis and histopathological examination results from biopsy supported the diagnosis of AGEP. The patient was then hospitalized and received steroid therapy. Within the first week of tapering off, the scales disappeared but the pustules increased. After such clinical findings, the histopathological examination results were revisited and reassessed. Thus, we considered changing the diagnosis to Pustular Psoriasis, and the therapy was switched to Methotrexate. The patient had a better outcome, and the pustules slowly disappeared entirely. Discussion: It is often difficult to differentiate between the pustules in pustular psoriasis and AGEP unless by thorough history-taking and physical examinations. AGEP is characterized by a widespread of pustules with an acute febrile onset; while pustular psoriasis is an acute variant of psoriasis where pustules are spread over erythematous skin and accompanied by high fever and leukocytosis. Conclusion: Histopathological examination is the gold standard for the establishment of pustular psoriasis diagnosis. The histopathological characteristics of pustular psoriasis and AGEP are difficult to differentiate. Therefore, we need detailed history-taking and physical examination to establish the diagnosis.